Pengembangan media ular tangga menggunakan metode tanya jawab pada pembelajaran matematika materi perkalian - Ratnawati; Dwi Novri Asmara; Nurjanah Nurjanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT Nurjanah, 2023. "The development of snakes and ladders media using the question and answer method in learning math multiplication material in class II SDN 11 Sitiung, Dharmasraya Regency. This research is motivated by a lack of understanding in learning math multiplication material. This study aims to develop media to make it easier for students to understand the material. This type of research and development uses Research and development (R&D) research. This snakes and ladders media development model uses the ADDIE (Analyze, Design, Develop, Implementation, and Evaluation) development model. The five stages are carried out through needs analysis, learner analysis, and material analysis. Then the validation of snakes and ladders media is validated by UNDHARI FKIP lecturers, the practicality is done by looking at the responses of educators and students, the effectiveness is seen from the results of the test questions provided. The results of developing snakes and ladders media were declared very valid. Valid means that the media that is carefully made has been validated and is suitable for use and developed with an average of 94.27% with a very valid category, the results of practicality with an average of 91.06% are categorized as very practical. which means that the media is suitable for use because it has been assessed for practicality in terms of media and practicality of time. The results of the effectiveness of the completeness of the results of students with an average of 90% are categorized as very effective, the media is suitable for use because the quality, quantity, and time are very effective. Thus it can be concluded that the snakes and ladders media made are very valid, practical, and effective for educators to use in teaching and learning. Keywords: Development, Math, Multiplication.